Dynamic Relationship between Oil Price and Inflation in Oil Exporting Economy: Empirical Evidence from Wavelet Coherence Technique - Adebayo, Tomiwa Sunday (Energy Economics Letters, 2020)
This paper examined the co-movement and causality between oil price and inflation using monthly data spanning between January 2007 and March 2020. The study employed the wavelet coherence techniques which are a new technique in economics and finance to verify the co-movement and causality simultaneously. Additionally, Granger and Toda Yamamoto's causality tests were deployed as a robustness check for the wavelet coherence techniques. Findings from the wavelet coherence technique reveal; (a) positive co-movement between the inflation and oil price between 2014M2 and 2017M1 at scale 4-8; (b) there is evidence of causality from oil price to inflation. Wavelet coherence technique revealed unidirectional causality running from oil price to inflation which is also confirmed by the Granger and Toda Yamamoto causality tests. To the author's understanding, no studies concerning oil price and inflation nexus in the case of Nigeria have deployed this technique. Based on these findings, recommendations were put forward.